Mutated NPM1 in patients with acute myeloid leukemia in remission and relapse. Issue 6 (June 2014) - Jain, Preetesh; Kantarjian, Hagop; Patel, Keyur; Faderl, Stefan; Garcia-Manero, Guillermo; Benjamini, Ohad; Borthakur, Gautam; Pemmaraju, Naveen; Kadia, Tapan; Daver, Naval; Nazha, Aziz; Luthra, Raja; et al.
Abstract Patients with newly diagnosed AML (n = 360) including 137 (38%) with normal karyotype (NK) were evaluated. Overall, 60 (16.6%) patients, including 46 of the 137 (33.5%) NK patients, had NPM1 mutation at baseline. Thirty-nine patients (30 NK) had available NPM1 status at the time of complete remission (CR) and all (100%) were negative for mutated NPM1. Among the patients with mutated NPM1 at baseline, 10/39 overall (25%) and 7/30 NK (23%) patients relapsed. NPM1 status was available for eight patients (six with NK) at the time of relapse. Among them, 7/8 overall (87%) and 5/6 NK (83%) patients had mutated NPM1, while 1/8 overall (12%) and 1/6 NK (16%) patients remained NPM1 wild type. Among the 300 patients (including 91 with NK) with wild type NPM1 at diagnosis, none acquired a mutated NPM1 clone, either at CR or at relapse. We conclude that mutated NPM1 is a stable and reliable prognostic marker in AML and can be used to assess MRD.